In-house cyclotron production of high-purity Tc-99m and Tc-99m radiopharmaceuticals. (September 2018) - Martini, Petra; Boschi, Alessandra; Cicoria, Gianfranco; Zagni, Federico; Corazza, Andrea; Uccelli, Licia; Pasquali, Micòl; Pupillo, Gaia; Marengo, Mario; Loriggiola, Massimo; Skliarova, Hanna; Mou, Liliana; et al.
Abstract: In the last years, the technology for producing the important medical radionuclide technetium-99m by cyclotrons has become sufficiently mature to justify its introduction as an alternative source of the starting precursor [ 99m Tc][TcO4 ] - ubiquitously employed for the production of 99m Tc-radiopharmaceuticals in hospitals. These technologies make use almost exclusively of the nuclear reaction 100 Mo( p, 2n ) 99m Tc that allows direct production of Tc-99m. In this study, it is conjectured that this alternative production route will not replace the current supply chain based on the distribution of 99 Mo/ 99m Tc generators, but could become a convenient emergency source of Tc-99m only for in-house hospitals equipped with a conventional, low-energy, medical cyclotron. On this ground, an outline of the essential steps that should be implemented for setting up a hospital radiopharmacy aimed at the occasional production of Tc-99m by a small cyclotron is discussed. These include (1) target production, (2) irradiation conditions, (3) separation/purification procedures, (4) terminal sterilization, (5) quality control, and (6) Mo-100 recovery. To address these issues, a comprehensive technology for cyclotron-production of Tc-99m, developed at the Legnaro National Laboratories of the Italian National Institute of Nuclear Physics (LNL-INFN), will be used as a reference example. Highlights: Direct production of Tc-99m by cyclotrons. Requisites for Mo-100 target production. Requisites for separation/purification of accelerator-produced [ 99m Tc][TcO4 ] - . Quality requirements for cyclotron-produced [ 99m Tc][TcO4 ] - suitable for clinical use.